Risedronate Attenuates Podocyte Injury in Phosphate Transporter-Overexpressing Rats - Yohei Asada; Takeshi Takayanagi; Tsukasa Kawakami; Eisuke Tomatsu; Atsushi Masuda; Yasumasa Yoshino; Sahoko Sekiguchi-Ueda; Megumi Shibata; Tomihiko Ide; Hajime Niimi; Eishin Yaoita; Yusuke Seino; et al. (International Journal of Endocrinology)
Osteoporosis patients with chronic kidney disease (CKD) are becoming common in our superaging society. Renal dysfunction causes phosphorus accumulation in the circulating plasma and leads to the development of CKD-mineral bone disorder (MBD). We have previously reported that type III Pi transporter-overexpressing transgenic (Pit-1 TG) rats manifest phosphate (Pi)-dependent podocyte injury. In the present study, we explored the effect of risedronate on Pi-induced podocyte injury in vivo. Pit-1 TG rats and wild-type rats at 5 weeks old were divided into a risedronate-treated group and an untreated group. We subcutaneously administered 5 μg/kg body weight of risedronate or saline twice a week during the experimental period. Risedronate did not alter serum creatinine levels at 5, 8, and 12 weeks of age. However, electron microscopy images showed that thickening of the glomerular basement membrane was improved in the risedronate treatment group. Furthermore, immunostaining for podocyte injury markers revealed that both desmin- and connexin43-positive areas were smaller in the risedronate-treated group than in the untreated group, suggesting that bisphosphonates could rescue Pi-induced podocyte injury. In conclusion, our findings suggest that risedronate could maintain glomerular barrier function by rescuing Pi-induced podocyte injury.